Topoisomerase II Inhibitors Induce DNA Damage-Dependent Interferon Responses Circumventing Ebola Virus Immune Evasion - Priya Luthra (American Society for Microbiology, 2017)
ABSTRACT Ebola virus (EBOV) protein VP35 inhibits production of interferon alpha/beta (IFN) by blocking RIG-I-like receptor signaling pathways, thereby promoting virus replication and pathogenesis. A high-throughput screening assay, developed to identify compounds that either inhibit or bypass VP35 IFN-antagonist function, identified five DNA intercalators as reproducible hits from a library of bioactive compounds. Four, including doxorubicin and daunorubicin, are anthracycline antibiotics that inhibit topoisomerase II and are used clinically as chemotherapeutic drugs. These compounds were demonstrated to induce IFN responses in an ATM kinase-dependent manner and to also trigger the DNA-sensing cGAS-STING pathway of IFN induction. These compounds also suppress EBOV replication in vitro and induce IFN in the presence of IFN-antagonist proteins from multiple negative-sense RNA viruses. These findings provide new insights into signaling pathways activated by important chemotherapy drugs and identify a novel therapeutic approach for IFN induction that may be exploited to inhibit RNA virus replication. IMPORTANCE Ebola virus and other emerging RNA viruses are significant but unpredictable public health threats. Therapeutic approaches with broad-spectrum activity could provide an attractive response to such infections. We describe a novel assay that can identify small molecules that overcome Ebola virus-encoded innate immune evasion mechanisms. This assay identified as hits cancer chemotherapeutic drugs, including doxorubicin. Follow-up studies provide new insight into how doxorubicin induces interferon (IFN) responses, revealing activation of both the DNA damage response kinase ATM and the DNA sensor cGAS and its partner signaling protein STING. The studies further demonstrate that the ATM and cGAS-STING pathways of IFN induction are a point of vulnerability not only for Ebola virus but for other RNA viruses as well, because viral innate immune antagonists consistently fail to block these signals. These studies thereby define a novel avenue for therapeutic intervention against emerging RNA viruses.